COVID-19 on the Telecommunications Industry Stock Market Performances: An Event-Study Approach - Pratita Garnis Ariantika; Arthik Davianti (Universitas Pendidikan Ganesha, 2021)
Covid-19's impact on the global economy is unclear. The stock market has responded with dramatic moves around the world. This study aims to analyze the quality of knowledge of the COVID-19 pandemic events regarding the performance of the Indonesian stock market as seen from the average abnormal return before and after the first case of COVID-19 Indonesia on March 2, 2020. The research design used in this study is an event study. The three samples used in this study are companies engaged in the telecommunications sub-sector on the Indonesia Stock Exchange. The sampling technique used in this research is purposive sampling. The study focused on a window period of 15 days before and 15 days after the event date. Hypothesis testing was carried out using the paired sample t-test on data with a typical distribution and the one-sample Wilcoxon signed-ranked test on data that were not normally distributed. The results obtained are that stocks react positively but not significantly to the announcement of the first case in Indonesia using an event study research design. There is a significant difference in abnormal returns before and after the first case of COVID-19 patients in Indonesia was announced.